A freestanding, hierarchically porous poly(imine dioxime) membrane enabling selective gold recovery from e‐waste with unprecedented capacity. Issue 6 (29th June 2022) - Li, Huaimeng; Ye, Mengxiang; Fu, Zhen; Zhang, Haimin; Wang, Guozhong; Zhang, Yunxia
Abstract: The ever‐growing depletion of precious metals in modern electronic industry necessitates unremitting exploitation of novel materials for gold recovery from e‐waste. Herein, a freestanding poly(imine dioxime) (PIDO) membrane has been successfully fabricated for highly efficient recovery of gold from e‐waste. The consummate integration of abundant binding sites and hierarchically porous architecture renders the resulting PIDO membrane with a record‐breaking uptake capacity (9250 mg g −1 ) toward gold, fast adsorption equilibrium time, as well as satisfactory regeneration and reusability. Furthermore, PIDO membrane is also well competent for selective gold recovery from waste central processing unit leachate with remarkable efficiency (>99%). Considering high recovery efficiency, outstanding selectivity, and simple/scalable production process, the proposed PIDO membrane will hold huge prospect in the sustainable recovery of gold from e‐waste. Abstract : A freestanding, hierarchically porous Poly(imine dioxime) membrane is fabricated via a simple evaporation‐induced self‐assembly technique based on the Marangoni effect. The resulting PIDO membrane demonstrates excellent gold recovery performance, including record‐breaking capacity, ultrafast kinetics, superior selectivity, outstanding regeneration and reusability. The work paves the way for the sustainable recovery of gold from e‐waste in an economical and feasible means.